Simulation and Analysis of High Voltage Engineering in Power Systems - Micu, Dan Doru (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book address important issues regarding the modelling and simulation tools and techniques that are applied in high-voltage engineering in modern power systems. The presented conceptual, constructive, empirical, experimental, and theoretical results are obtained in the area of high-voltage engineering. Special attention is given to protection methods against direct lightning strikes, partial discharge tests, discharges' influence on different structures, cable screening, and induced voltages, among others.